2004
DOI: 10.1207/s15328015tlm1603_2
|View full text |Cite
|
Sign up to set email alerts
|

Arts-Related Activities Across U.S. Medical Schools: A Follow-Up Study

Abstract: Utilization of the arts serves four major functions: (a) enhancement of student well-being, (b) improvement of clinical skills, (c) promotion of humanism, and (d) employment by students as a teaching tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 7 publications
2
29
0
1
Order By: Relevance
“…Our students reported being equipped, as the Institute of Medicine implored, ''with the knowledge and skills from the behavioral and social sciences needed to recognize, understand, and effectively respond to patients as individuals, not just their symptoms'' (Cuff & Vanselow 2004). This theme is similar to other researchers who have suggested that humanities can provide space for students to reflect on their own experiences and emotions and consider what it means to be a doctor (Rodenahuser et al 2004;Lewis 2011;Mullangi 2013;Karkabi et al 2014). Humanities allow students to reconnect with what it means to be human, improve empathy skills, and move beyond storytelling to ''story listening'' (Hurwitz & Charon 2013).…”
Section: Discussionsupporting
confidence: 69%
“…Our students reported being equipped, as the Institute of Medicine implored, ''with the knowledge and skills from the behavioral and social sciences needed to recognize, understand, and effectively respond to patients as individuals, not just their symptoms'' (Cuff & Vanselow 2004). This theme is similar to other researchers who have suggested that humanities can provide space for students to reflect on their own experiences and emotions and consider what it means to be a doctor (Rodenahuser et al 2004;Lewis 2011;Mullangi 2013;Karkabi et al 2014). Humanities allow students to reconnect with what it means to be human, improve empathy skills, and move beyond storytelling to ''story listening'' (Hurwitz & Charon 2013).…”
Section: Discussionsupporting
confidence: 69%
“…Although medical humanities courses are increasing quantitatively in the curricula of medical faculties during last decades, there are not many studies investigating the efficacy of such programs (Rodenhauser et al 2004). A few studies pointing to efficacy, indicate that medical humanities programs are beneficial for strengthening the students' empathy, deepening their understanding, enabling them to manage conflict, helping them to express themselves more efficiently, endowing them with a social and humanistic perspective, making them grasp life experiences related to medical practice and develop a new line of insight (Shapiro & Hunt 2003;Shapiro et al 2005;Lee & Ahn 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As a reflection of all the above-mentioned changes, during the last decades, medical humanities programs have been added to the undergraduate and graduate curricula of a number of medical schools. (Rodenhauser et al 2004) Humanities in medicine…”
Section: Practice Pointsmentioning
confidence: 99%
See 2 more Smart Citations